2021
DOI: 10.1029/2020jc016994
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Mass Properties and Circulation in the Deep and Abyssal Philippine Sea

Abstract: In the deep/abyssal layers, water-masses from the Southern Ocean and the Northeastern Pacific spill into the Philippine Sea and upwell into the intermediate layers , which are assumed to play a significant role in modulating the regional water-mass properties and overturning circulation.The Lower Circumpolar Deep Water (LCDW) covers the abyssal layer of the northwestern Pacific (e.g., Siedler et al., 2004). Characterized by maxima of salinity and dissolved oxygen and minima of potential temperature and dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
4
10
0
Order By: Relevance
“…Nearly zero transport through the channel at 134.9°E/12°N is also consistent with the observed fact that the LCPW cannot penetrate the Southern Philippine Basin (Tian et al., 2021). Consistent with geostrophic velocity inferred from hydrographic measurement at 137°E (Tian et al., 2021, their Figure 8), the modeled U along at 136.9°E/23.29°N has a core speed of ∼3 cm s −1 , much smaller than that at KPRM. This yields nearly zero transport through this channel during the measurement period.…”
Section: Resultssupporting
confidence: 86%
“…Nearly zero transport through the channel at 134.9°E/12°N is also consistent with the observed fact that the LCPW cannot penetrate the Southern Philippine Basin (Tian et al., 2021). Consistent with geostrophic velocity inferred from hydrographic measurement at 137°E (Tian et al., 2021, their Figure 8), the modeled U along at 136.9°E/23.29°N has a core speed of ∼3 cm s −1 , much smaller than that at KPRM. This yields nearly zero transport through this channel during the measurement period.…”
Section: Resultssupporting
confidence: 86%
“…The distribution of the drifts and their adjacent moats along the southern to southwestern side of the seafloor highs (Figures 2 and S2 in Supporting Information S1) suggests Coriolis force-induced westward water mass circulation (Faugères et al, 1999;Rebesco et al, 2014) that matches the PDW circulation (Nagano et al, 2018;Talley et al, 2011). The two contourite depositional systems are consistent with PDW's present-day location and water depth at 1,000-4,500 m below the sea level (Kaneko et al, 2001;Talley et al, 2011;Tian et al, 2021; Figures 1d and 1e). Hence, the chronologically consistent sedimentation patterns and stratigraphic discontinuities in the two systems provide an opportunity to discuss their evolution and formation by PDW circulation, and to use them as proxy to reconstruct long-term variations in PDW circulation.…”
Section: Regional Correlations In Contourite Seismic Stratigraphysupporting
confidence: 71%
“…Subduction zone from Müller et al., 2016. Ocean circulation compiled from Kawabe & Fujio, 2010; Talley et al., 2011; Nagano et al., 2018; Tian et al., 2021. (b) Bathymetric map at International Ocean Discovery Program Site U1437 with seismic lines.…”
Section: Introductionmentioning
confidence: 99%
“…Based on mooring data, Siedler et al (2004) suggested that 0.36 Sv LCPW flows into the West Mariana Basin via the junction. Tian et al (2021) proposed that since the junction is the only channel deeper than ~4000 m connecting to the Philippine Sea, the LCPW enters the sea through the junction area. Zhai and Gu (2020) suggested that because of the blockage of the Yap Ridge, the main body of the LCPW flowing from the East Mariana Basin enters the Philippine Sea via the Mariana Trench and the junction.…”
Section: Flow Path In Yap-mariana Junctionmentioning
confidence: 99%
“…Zhai and Gu (2020) suggested that because of the blockage of the Yap Ridge, the main body of the LCPW flowing from the East Mariana Basin enters the Philippine Sea via the Mariana Trench and the junction. In studies by Zhai and Gu (2020) and Tian et al (2021), the LCPW incoming area of the Philippine Sea corresponds to the West Mariana Basin.…”
Section: Flow Path In Yap-mariana Junctionmentioning
confidence: 99%